PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PT. BPRS AMANAH INSANI BEKASI - Nanda Rodiyana; Elyas Purba Prastiya; Ibrahim Bali Pamungkas (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this study was to determine how much positive and significant influence on the environment and communication partially or simultaneously on the performance of employees at PT. Insani Amanah BPRS. The object of this research is all employees at PT. Insani Amanah BPRS. The type of research used in this research is descriptive quantitative. Methods of data collection using observation and questionnaires. The sampling technique used a saturated sample with the number of respondents as many as 40 employees. The validity of the data in this study used the Validity Test, Reliability Test, and Classical Assumption Test. The result of this study is that there is a positive and significant influence partially or simultaneously between the Work Environment and Communication on the Performance of Employees of PT. BPRS Amanah Insani Bekasi.